Training participation of a firm's aging workforce - Pfeifer, Christian [Verfasser]; Janssen, Simon [Verfasser]; Yang, Philip [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2012)
"We use a long panel data set for four cohorts of male blue-collar workers entering into an internal labor market to analyze the effect of age on the probability of participating in different employer-financed training measures. We find that training participation probabilities are inverted u-shaped with age and that longer training measures are undertaken earlier in life and working career. These findings are consistent with predictions from a human capital model that incorporates amortization period and screening effects." The authors use personnel data of a large German company from the energy sector located in West Germany. The data contain a subsample of 438 blue-collar workers in the company's mining business. All of these workers entered the firm in four subsequent cohorts, from 1976 until 1979, and stayed in the company over the entire observation period up to the year 2002. (Autorenreferat, BIBB-Doku)
Keywords: P 1.8 Ältere; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; S 1.5.3 Betriebliche Weiterbildung; S 4.3.6 Human Capital; Älterer Arbeitnehmer; Qualifizierung; Betriebliche Weiterbildung; Interner Arbeitsmarkt; Weiterbildungsbeteiligung; Bildungsinvestition; Humankapitalansatz; Einflussfaktor; Lebensalter